Goal-Directed Oxygen Delivery and Risk of Acute Kidney Injury after Cardiac Surgery - AHMAD, AQEEL; MUHAMMAD, ARZ; ZAFAR, FAUZIA; TUFAIL, QAZI M.; AWAN, ABAD-UR-REHMAN; RIAZ, KASHIF (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Oxygen delivery (DO2) to the heart during the cardiopulmonary bypass is important in order to sustain the perfusion of tissues in heart surgery patient and hence avoid postoperative complication. Poor DO2 has been linked with dysfunction of the organ mainly acute kidney injury (AKI), long-term ventilation, and early death. To test the relationship between intraoperative oxygen delivery levels during cardiopulmonary bypass with clinical outcomes postoperative and to compare the outcome between goal-directed DO2 -guided perfusion and conventional methods of perfusion in cardiac surgery patients. Methodology: The proposed analytical observational study was carried out at Department of Cardiothoracic Surgery, Shaikh Zayed Hospital Lahore from between 1st June 2023 to 30th November 2024. Eighty-nine adult patients that had undergone cardiac surgery and cardiopulmonary bypass were sampled using consecutive sampling. Intraoperative calculation of oxygen delivery (DO2) was done based on standard perfusion equations and patients were divided into groups of goal-directed DO2 strategy and conventional perfusion. The main outcomes were postoperative acute kidney injury, protracted ventilation and mortality in hospital. The intraoperative parameters were monitored (pump flow, hemoglobin, temperature and mean DO2). Results: Low oxygen supply below the critical levels was linked to the worsened postoperative complications, such as acute kidney injury and extended ventilation. The patient with a goal-directed DO₂ approach had a much lower ratio of acute kidney injury in comparison to the patients treated with conventional management of the perfusion (p < 0.05). They did not find any significant difference between transfusion requirements or mortality of the groups. The multivariate analysis revealed that the below critical threshold oxygen delivery, diabetes mellitus, preoperative anemia, decreasing left ventricular ejection fraction, and highest hematocrit values were important predictors of in-hospital mortality. Conclusion: Poor delivery of oxygen during cardiopulmonary bypass is largely linked with the poor outcome in postoperative patients under cardiac surgery. The perfusion strategies of goal-oriented DO2 can potentially prevent acute kidney injury without raising the need in transfusion or death. In resource constrained scenarios like Pakistan, optimization of delivery of oxygen during cardiac surgery can help increase patient outcomes.